2018
DOI: 10.17546/msd.448923
|View full text |Cite
|
Sign up to set email alerts
|

Work-related fatigue and related factors among nurses working at the Adnan Menderes University Hospital

Abstract: As a result of fatigue, performance issues develop at work, poor concentration, attention deficit, problem-solving and decision-making difficulties, memory impairment, delay in response time, professional incompetence and problems in private and social life occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
3
0
3
Order By: Relevance
“…Even after adjusting for confounding variables, work department had a significant influence on nurses’ physical and mental fatigue. Some prior studies have reported that the work department is related to nurse fatigue although one study suggested the opposite—that the work department is not a factor influencing the fatigue of nurses [ 13 , 19 , 21 ]. Such a gap may have occurred due to different classifications of work departments in each study, making direct comparisons between them more difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after adjusting for confounding variables, work department had a significant influence on nurses’ physical and mental fatigue. Some prior studies have reported that the work department is related to nurse fatigue although one study suggested the opposite—that the work department is not a factor influencing the fatigue of nurses [ 13 , 19 , 21 ]. Such a gap may have occurred due to different classifications of work departments in each study, making direct comparisons between them more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Level of fatigue varies by work department as well. Emergency room (ER) nurses are more likely to experience high levels of fatigue relative to nurses working in other nursing departments [ 1 , 13 ]. This discrepancy is attributed to the characteristics of these respective special care departments, including the need to manage complicated and life-threatening medical problems, the existence of physically and mentally demanding job requirements, the persistence of increased pressure to perform well, and the use of complex technologies [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pada penelitian lain yang dilakukan Noviyanti, 2020 juga menemukan hal serupa dimana terdapat hubungan antara usia dengan kelelahan (10). Sama halnya dengan hasil penelitian yang dilakukan oleh Ozvurmaz dan Mandiracioglu, 2018 di turki yang menunjukkan bahwa terdapat hubungan antara usia dengan kelelahan kerja pada perawat (11). Dalam penelitian ini, usia berkaitan dengan terjadinya kelelahankerja pada perawat.…”
Section: Pembahasanunclassified
“…Thus having very less sun exposure is leading to manifestations of hypovitaminosis D [ 7 ]. Surprisingly it’s the medical community which are at high risk for hypovitaminosis [ 8 - 11 ]. The ICU staff, the operation theatre staff and critical care team are under serious threat of hypovitaminosis.…”
Section: Sun Exposure/sun Shinementioning
confidence: 99%